Justify your alpha - Lakens, D; Adolfi, FG; Albers, CJ; Apps, MAJ; Collins, GS; Parsons, S; Et al. (Springer Nature, 2018)
In response to recommendations to redefine statistical significance to P ≤ 0.005, we propose that researchers should transparently report and justify all choices they make when designing a study, including the alpha level.